2021
DOI: 10.1002/nop2.814
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and coping strategies: How they influence quality of life in Iranian women with breast cancer

Abstract: Aim To investigate the mediation/moderation effect between Coping Behaviors (CBs) and Sense of Coherence (SOC) in the prediction of health‐related quality of life (HRQoL) in breast cancer patients. Design Cross‐sectional. Methods A total of 221 patients were included in this study. The 13‐item Orientation to Life Questionnaire, Brief COPE and Functional Assessment of Cancer Therapy—Breast were investigated. Pearson's correlation coefficient and mediation/moderation analysis were performed. Results Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
1
7
0
1
Order By: Relevance
“…Last but not least, two notable limitations of the applied modeling approach were the lack of considering the interplay between the mediators and equivalence models. For instance, in terms of the former, some studies suggest the mediation effect of sense of coherence between the coping strategies and HRQoL relationship ( Zamanian et al, 2021a ) and the complex network of influence among resistance resources ( Cecon et al, 2021 ). In terms of the latter, it could be hypothesized that patients with lower physical wellbeing and arm functionality could be more vulnerable to experience stigmatization since social devaluations are suggested to occur more in the face of observable body deformation ( Goffman, 1963 ; Pachankis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Last but not least, two notable limitations of the applied modeling approach were the lack of considering the interplay between the mediators and equivalence models. For instance, in terms of the former, some studies suggest the mediation effect of sense of coherence between the coping strategies and HRQoL relationship ( Zamanian et al, 2021a ) and the complex network of influence among resistance resources ( Cecon et al, 2021 ). In terms of the latter, it could be hypothesized that patients with lower physical wellbeing and arm functionality could be more vulnerable to experience stigmatization since social devaluations are suggested to occur more in the face of observable body deformation ( Goffman, 1963 ; Pachankis et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The more the patients feel that there are SOC available to them, the more likely they perceive cancer as a manageable challenge, and consequently, they can perceive life as more meaningful ( Langius-Eklöf et al, 2008 ; Lashani et al, 2021 ). For Iranian women with breast cancer, SOC has been a better predictor of HRQoL compared to coping strategies ( Rohani et al, 2015 ; Zamanian et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de sua incidência crescente em todo o mundo, terapias médicas avançadas e exames precoces nas últimas décadas levam a uma diminuição das taxas de mortalidade. Por ter relativamente bom prognóstico, ocupa o quinto lugar como causa de morte entre os cânceres, mesmo embora seja o mais comum (ZAMANIAN et. al., 2021).…”
Section: Resultsunclassified
“…Zamanian et al conducted a study of a group of 221 women with breast cancer and observed a positive correlation between the sense of coherence and quality of life. They concluded that practical activities aimed at reinforcing the sense of coherence in women should be included in rehabilitation programmes [ 50 ]. According to Colomer-Pérez et al, reinforcing the sense of coherence in nurse assistants through a salutogenic education strategy increases their health resources and contributes to higher resistance to work-related stress [ 51 ].…”
Section: Discussionmentioning
confidence: 99%